2021
DOI: 10.1108/bij-11-2020-0574
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of Singapore maritime cluster: the role of cluster facilitators

Abstract: Purpose This article analyses the role of cluster facilitators in the Singapore maritime cluster. Singapore has been recognised for its pro-business policies and its ability to attract international shipping companies to set up the ship ownership headquarters and ship management activities in Singapore. Design/methodology/approach The research is an empirical investigation on the approach for industrial cluster development of the Singapore maritime clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 71 publications
0
0
0
Order By: Relevance
“…Singapore is also the world's leading marine fuel bunkering port (ranked 1st), with 49.8 million tons of petroleum bunkered in 2020 for deep-sea ships [14]. Additionally, Zhang et al [15] found that Singapore-based shipping companies are more inclined to accept alternative fuels. As mentioned earlier, alternative fuel options that may be possible for inland or short-sea vessels may not meet the needs of ships meant for deep-sea transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Singapore is also the world's leading marine fuel bunkering port (ranked 1st), with 49.8 million tons of petroleum bunkered in 2020 for deep-sea ships [14]. Additionally, Zhang et al [15] found that Singapore-based shipping companies are more inclined to accept alternative fuels. As mentioned earlier, alternative fuel options that may be possible for inland or short-sea vessels may not meet the needs of ships meant for deep-sea transportation.…”
Section: Introductionmentioning
confidence: 99%